Grindability and kinetic study during pyrolysis of raw and torrefied Leucaena Leucocephala: article - Ahmad Zaidi, Ahmad At-Tarmidzie; Matali, Sharmeela
Malaysia is a country that is highly dependent on fossil fuel energy as the main energy source. This has been a problem for the country because for a fact, fossil fuel is an energy source that is not renewable and will be depleted over the years. Biomass is one of the potential alternatives for fossil fuel replacement due to its traits being renewable. The reason Malaysia does not fully utilize its renewable energy resource because Malaysia is lacking in biomass conversion technology and its application. Malaysia is still comfortable with the usage of fossil fuel resource because of their lack of awareness. Direct combustion of biomass is the most promising method to exploit biomass to produce energy. However, one of the method’s drawbacks is the difficulty to grind the product to obtain fine particles. To improve the properties of raw biomass, torrefaction or mild pyrolysis is considered. Therefore, for this research, the grindability and kinetics study during pyrolysis need to be carried out to obtain the best way to produce high quality bioenergy feedstock. Biomass chosen for this research project, Leucaena Leucocephala (LL) as a type of potential energy crop, was chosen as the raw material. The torrefaction was done under the temperature range from 200⁰C to 300⁰C. Torrefied biomass pellet was compared to its raw pellet in terms of its grindability and its kinetics parameter through Coats-Redfern, chemical non-isothermal kinetic method. From the results obtained, pyrolysis of biomass does increase the grindability properties of the biomass pellets and its activation energy (Ea) significantly. As the temperature of torrefaction increases, comparing the raw pellets and pellets that is torrefied at 300⁰C, the weight percentage of particle size below 100 μm of grinded pellets increases from 26.94% to 62.31%. Meanwhile for the activation energy (Ea), the value decreases as the torrefaction temperature was increased. It means that the higher temperature of torrefied pellets requires less activation energy thus improving the kinetics properties of the torrefied pellets as the value of activation energy of raw pellets is 119.8 kJ/mol meanwhile for pellets that is torrefied at 300⁰C is 82.9 kJ/mol. It is found that during pyrolysis, raw Leucaena Leucocephala (LL) followed Third Order (F3) reaction mechanism.